(3fgGjI GdWdH aj TQM GdecJSHs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3CHh GdbGSe eMeO Hf CMeO GdSjeGhj GdYQGbjs ((3Shjaj Hf CMeO GdLHd GdYOhj s)
(3ChdgG (B:s
(3GdMeO ddg dGYdGej HCSQGQ eNdhbGJg CeG HYO aGdebOeI dgPG GdcJGH Cf fbhd CfG deG CcdefG eG GQGO Gddg GceGdg ef GdSfhjf GdeJbOejf ef LedI gPG GdcJGH s
(3BNQgG (B:s
(3hbO Je GdSaQ GdKGdK ef cJGH fgGjI GdWGdH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs